The Value of Radiotherapy for Advanced Non-Small Cell Lung Cancer With Oncogene Driver-Mutation - Cui, Jinfeng; Li, Li; Yuan, Shuanghu (Frontiers in Oncology, 2022)
Due to the widespread use of tyrosine kinase inhibitors (TKIs), which have largely supplanted cytotoxic chemotherapy as the first-line therapeutic choice for patients with advanced non-small cell lung cancer (NSCLC) who have oncogene driver mutations, advanced NSCLC patients with oncogene driver mutations had much long median survival. However, TKIs’ long-term efficacy is harmed by resistance to them. TKIs proved to have a limited potential to permeate cerebrospinal fluid (CSF) as well. Only a small percentage of plasma levels could be found in CSF at usual doses. Therefore, TKIs monotherapy may have a limited efficacy in individuals with brain metastases. Radiation has been demonstrated to reduce TKIs resistance and disrupt the blood-brain barrier (BBB). Previous trials have shown that local irradiation for bone metastases might improve symptoms, in addition, continuous administration of TKIs combined with radiotherapy was linked with beneficial progression-free survival (PFS) and overall survival (OS) for oligometastasis or bone metastasis NSCLC with oncogene driver mutations. The above implied that radiotherapy combined with targeted therapy may have a synergistic impact in patients with advanced oncogene driver-mutated NSCLC. The objective of this article is to discuss the value of radiotherapy in the treatment of those specific individuals.